Ambiência monástica e prática litúrgico-musical pós-tridentinas no mosteiro de S. Bento de Cástris - Conde, Antónia Fialho (2016)
Abstract In the current historiographical production there is a manifest interest for the history of female religiosity. The mystic phenomenon, the everyday life and the temporal dimension of the communities, in terms of familiar and social connection to the outside of cloistered spaces, manifestations of creativity and culture, are increasingly treated issues. This interest is also expressed about the Cistercian Order in Portugal. In the female branch, the monastery of St. Benedict of Cástris, officially Cistercian for more than 700 years, has been the target of an interdisciplinary approach that intents to appreciate the impact of the reflections of the Council of Trent in the musical praxis of the nuns. This community, subject to Alcobaça and controlled through Visitors, registers in its documentation not only the presence of nuns that sang and played various instruments, arising mainly from Évora region, a city with a recognized musical tradition, but also registers various expenses related with the musical practice of the monastery. Resumo Regista-se, na actual produção historiográfica, um interesse manifesto pela história da religiosidade feminina. O fenómeno místico, o viver quotidiano e a dimensão temporal das comunidades, em termos de ligação familiar e social ao exterior dos espaços-clausura, as manifestações de criatividade e cultura, são questões cada vez mais tratadas. Esse interesse manifesta-se também para a Ordem de Cister em Portugal, sendo que, no ramo feminino, o mosteiro de S. Bento de Cástris, oficialmente cisterciense há mais de 700 anos, vem sendo alvo de uma abordagem multidisciplinar que procura apreciar os reflexos do Concílio de Trento na praxis musical das religiosas. Esta comunidade, sujeita a Alcobaça e por ela controlada através dos Visitadores, regista na sua documentação não só a presença de religiosas cantoras e tangedoras de vários instrumentos, oriundas maioritariamente da região de Évora, cidade com uma tradição musical reconhecida, como diversas despesas relacionadas com a prática musical do mosteiro.